First zoeal stage of the snapping shrimps Alpheus formosus Gibbes, 1850 and Alpheus malleator Dana, 1852 (Caridea: Alpheidae), with new characters to the genus - Pasinatto, Karmine; Mantelatto, Fernando L.; Terossi, Mariana (Zootaxa, 2020)
The first zoeae of Alpheus formosus Gibbes, 1850 and Alpheus malleator Dana, 1852 are described and illustrated for the first time, based on laboratory-hatched larvae from parental females sampled in Vitória Island, Ubatuba, Brazil. Both species shared many characters with other species of genus Alpheus Fabricius, 1798, but they also have some exclusive characters as 10 setae on the basis of the maxilla, first maxilliped with endopod 2-segmented and exopod 4-segmented, second maxilliped with exopod 4-segmented, presence of bud only of the first pereopod, presence of anal spine and simple dorsal setae on the pleon. The zoea I of both species, nevertheless, can be separated by segmentation in the exopod of the antenna (8 in A. formosus, 6 in A. malleator); segmentation in the endopod and exopod of the third maxilliped (5 in A. formosus and 4 in A. malleator); peduncle of antennule 3-segmented in A. formosus (unsegmented or 2-segmented in other species) and presence of a medial tubercle in the proximal segment in the exopod of the antenna of A. malleator (absent in A. formosus, not reported in all other species). In this study three new characters are proposed to be analyzed in zoea of the genus Alpheus: presence of anal spine in both species (absent in Alpheus saxidomus Holthuis, 1980, but not reported in other species) and for the first time reported, presence of a tubercle in the exopod of the antenna (present only in A. malleator) and presence of simple dorsal setae on the pleon (both species), here analyzed under light and scanning electron microscopy.